Performance Evaluation Of Optical CDMA Ring Network Due To Self Interference Induced By Power Circulation - Mohamed Ashari, Zool Hilmi (2008)

(untitled)
Presently, there is great interest in the telecommunication research community and industries on the optical code multiple access (OCDMA) techniques. This is due to the huge bandwidth offered by the optical link, highly efficient optical signal processing and decreasing cost of optical components. The performance of OCDMA systems depend on the code properties and detection scheme. In this thesis, an OCDMA system for a ring topology based on K-S code was proposed to be implemented in the metro environment. K-S code is a new code for Optical CDMA with variable weight greater than 2. In this thesis the weight of 4 is chosen. The code possesses ideal cross correlation properties which can reduce multiple access interference (MAI) and noise. However, there are two main types of interferences exist in the OCDMA ring topology. Besides MAI, there are another interference due to the circulation of power in the ring namely self–interference. It will deteriorate the next concurrent data stream for the same user to be transmitted into the ring and could make the system performance decreased.A direct detection scheme was used to eliminate MAI and hence only the effect of self-interference was investigated. Before performing the simulation, limited theoretical results on receive power were developed to show the trend of receive power at each receiver. The formula is depended on the transmitted power, fiber length, coupling ratio, number of nodes and the number of circulating power in the ring. The performance of the ring network was then simulated using commercial simulation software, OptiSystem Version 5.0. The network performance is evaluated against several design parameters by comparing the signal turns in the first and second transmission by referring to the bit error rate, BER, received power, Psr and the eye patterns. In this thesis, it was found that the effect of the self-interference is determined by the transmitted power, fiber length, coupling ratio and the bit rate. It proves that the self-interference is increased with the increment of transmitted power. It also experience losses with the increment of fiber span but the system will suffer the serious effect when the fiber length is shorter than 30 km at 1Gbps. Results also proves that the self-interference effect is worst at 30% coupling ratio although the system performance is better with the increment of coupling ratio until certain point. Finally, the best transmission rate for this system is 1Gbps while there were another optimum values for each parameter supported by the system in order to minimize the self-interference.